Finite-Time Current Tracking in Boost Converters by Using a Saturated Super-Twisting Algorithm - Juan-Eduardo Velázquez-Velázquez; Rosalba Galván-Guerra; José-Antonio Ortega-Pérez; Yair Lozano-Hernández; Raúl Villafuerte-Segura (Complexity)
The power converters are widely used in several industrial applications where it is necessary to obtain from a fixed voltage another one higher or lower than the original. In this paper, we focus on the DC-DC (direct current) boost converters, where to guarantee the desired voltage, an internal current tracking loop is usually used. However, this tracking cannot be assured in the presence of unknown load changes and external perturbations when traditional controller strategies are implemented. In this paper, an advanced control strategy is proposed to ensure the current tracking using a saturated super-twisting controller on the power converter. The finite-time current tracking of a DC-DC boost converter is assured in the presence of bounded Lipschitz perturbations composed by unknown load changes and exogenous signals. The proposed approach generates a continuous bounded control signal applied to the converter by using a sigma-delta modulator ΣΔM. The controller gains are tuned to obtain finite-time stabilization of the tracking error, while the control signal remains bounded. To illustrate the effectiveness of the proposed results, the controller is applied to a physical boost converter using the hardware implemented ΣΔM and an STM32 Discovery development card. Besides, the controller is compared with a first-order sliding mode controller showing that for small sample times, the energy of the error signal is reduced.